ANALYSIS OF SOCIAL ATTITUDES OF ELEMENTARY SCHOOL LEARNERS WITH THE APPLICATION OF ALBERT BANDURA'S LEARNING THEORY - Muhammad Feri; Naila Husna (Universitas Pendidikan Indonesia, 2022)
Education is not only to gain knowledge, but the education carried out must be able to improve social attitudes for students. This study aims to determine the difference in social attitudes of the class that implements Albert Bandura's social learning theory and the class that does not implement Albert Bandura's social learning theory. The approach used in this research is a quantitative approach with a Quasy Experimental Design with a Nonequivalent Control Group Design research pattern. This design applies two groups of students, namely the Experiment Class and the Control Class. Furthermore, in each class a pretest before treatment and posttest after treatment was carried out with six aspects of social attitudes, where each aspect consisted of three indicators. The experimental class carried out learning by applying Alber Bandura's social learning theory while the control class carried out learning without Albert Bandura's social learning theory. The results of the study generally show that there are differences in the acquisition of social attitude scores of the experimental class and the control class. The N-Gain score in the experimental class is 0.5 in the medium category. Meanwhile, in the control class, the N-Gain score was 0.216 in the low category